Alanine-fortified tomatoes relieve the acute alcohol-induced adverse effects in healthy men: a randomized cross-over study. Issue 1 (December 2016) - Oshima, Shunji; Shiiya, Sachie; Tokumaru, Yoshimi; Kanda, Tomomasa
Abstract Background Little is known about the effects of dietary components on the regulation of the gastric emptying rate of alcohol and its impact on alcohol metabolism. We recently found that the crude water-insoluble dietary fibers from several types of botanical foods maintained aqueous ethanol solutions. Additionally, the ethanol-absorbing ability of the dietary fibers correlated with the inhibition of the blood ethanol elevation by delaying gastric emptying. Moreover, we found that the synergism between tomatoes and alanine to reduce the absorption of alcohol in rats was attributable to the effect of alanine on precipitates, such as the crude water-insoluble dietary fibers of tomatoes. In the present study, we assess whether an alanine-fortified tomato (AFT) is effective in relieving acute alcohol-induced adverse effects by lowering the alcohol action in healthy human volunteers following the ingestion of alcohol with a meal. Methods Twenty healthy males ingested the AFT or sugar as the control, with 1.2 g/kg of alcohol and a micronutrient-fortified meal in a randomized cross-over study. Breath alcohol concentrations were temporally measured, and blood and urine samples were obtained during the trial. The study protocol was repeated with the AFT and sugar groups reversed 4 weeks later. Results Various analyses were performed using the data from the 15 subjects. The breath alcohol concentrations significantly decreased when AFT was ingested. A decrease in the urinary pH was also noted following the ingestion of AFT. Moreover, the sum of seven sedative scores as subjective sensation after alcohol ingestion was significantly reduced by AFT the next morning. Conclusions Our study demonstrates that the simultaneous ingestion of AFT under the consumption of excess alcohol and a micronutrient-fortified meal relieved the acute alcohol-induced adverse effects in male volunteers. These results are consistent with the effectiveness observed in rats as previously reported.